The effects of supplementation of probiotics, prebiotics, or synbiotics on patients with non-alcoholic fatty liver disease: A meta-analysis of randomized controlled trials - Xing, Wenmin; Gao, Wenyan; Lv, Xiaoling; Zhao, Zhenlei; Mao, Genxiang; Dong, Xiaoyan; Zhang, Zuyong (Frontiers in Nutrition, 2022)
Background Non-alcoholic fatty liver disease (NAFLD) is the most prevalent chronic liver disease. Research on the efficacy of probiotics, prebiotics, and synbiotics on NAFLD patients continues to be inconsistent. The purpose of this study is to evaluate the effectiveness of these microbial therapies on NAFLD. Methods Eligible randomized-controlled trials reporting the effect of probiotics, prebiotics, or synbiotics in NAFLD were searched in PubMed, Web of Science, Embase, Google scholar, and CNKI databases from 2020 to Jul 2022. The changes in the outcomes were analyzed using standard mean difference (SMD) and 95% confidence intervals (CIs) with a random- or fixed-effects model to examine the effect of microbial therapies. Subgroup analysis, influence and publication bias analysis were also performed. The quality of the eligible studies was evaluated using the Cochrane Risk of Bias Tool. Results Eleven studies met the inclusion criteria involving 741 individuals. Microbial therapies could improve liver steatosis, total cholesterol (TC), triglyceride (TG), low-density lipoprotein (LDL-c), alanine aminotransferase (ALT), alkaline phosphatase (ALP), glutamyl transpeptidase (GGT), and homeostasis model assessment-insulin resistance (HOMAI-R) (all P < 0.05). But microbial therapies could not ameliorate body mass index (BMI), energy, carbohydrate, fat intake, fasting blood sugar, HbA1c, insulin, high-sensitivity C-reactive protein (hs-CRP), and hepatic fibrosis of patients with NAFLD. Conclusion Probiotics, prebiotics, and synbiotics supplementation can potentially improve liver enzymes, lipid profiles, and liver steatosis in patients with NAFLD.